Ciclo de vida empresarial e qualidade da informação contábil das companhias abertas brasileiras - Costa, Wando Belffi da (2015)
This dissertation aims to identify whether the several life cycle stages (LCS) are related to the quality of accounting information in Brazilian companies. According to international research, those stages influence the quality of accounting information. The relevance, timing and conservatism metrics were apllied similar to the way used by Lopes (2009) to check the quality of accounting information. To identify the life cycle stages, it was used the organic identification elaborated by Dickinson (2011), wherein signals from the company cash flows are used to identify which lifecycle stage is the company in. The sample of this study consists in Brazilian publicly traded firms on the BM&FBovespa from 2008 to 2013. Although financial firms were excluded from the sample. The total amount of firms investigated was 330, summing up a total of 1,163 observations for the relevance model, 1,163 for the timing model and 1.167 observations for the conservatism model. In order to verify the effects of LCS in the quality of accounting information it was used an unbalanced panel data, robust regression with White correction, identifying LCS by means of dummies. The results indicate that the LCS affects the quality of accounting information and the stages of growth and maturity in the financial statements have greater relevance and timeliness. This study was not able to identify the effects of the stages LC in conservatism, since the variables of interest were not statistically significant.